ChemInform Abstract: Copper‐Catalyzed Trifluoromethylation of Alkenes: Synthesis of Trifluoromethylated Benzoxazines. Issue 50 (December 2015) - Jana, Sadhan; Ashokan, Athira; Kumar, Shailesh; Verma, Ajay; Kumar, Sangit
Abstract: A base and ligand free Cu‐catalyzed method for the construction of trifluoromethylated benzoxazines (III), (V), and (VII) is developed.